Titled Women and Voluntary War Work in Ireland during the First World War: a case study of Ethel, Lady Inchiquin. Issue 3 (16th April 2018) - O'Riordan, Maeve
ABSTRACT: This article uses microhistorical methods to explore the voluntary war-work activities of titled women in Ireland. It takes a case study of Ethel, Lady Inchiquin, who lived at Dromoland Castle in County Clare. By focusing on the activities of one particular woman, who did not achieve any considerable fame for her wartime activity, it is possible to deepen our understanding of the challenges faced by women of this class during a period of change in Ireland. These women, like their husbands, wished to retain the patriarchal status quo. The activities in which women like Lady Inchiquin engaged were not carried out in an attempt to further the reach of the acceptable sphere of female activity, but rather in an attempt to demonstrate their loyalty to the cause of the Empire.